2022
DOI: 10.3390/life12060874
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Difference between Female and Male Ussuri Catfish (Pseudobagrus ussuriensis) in Brain and Gonad Tissues

Abstract: DNA methylation has been found to be involved in sex determination and differentiation in many aquaculture species. The Ussuri catfish (Pseudobagrus ussuriensis) is a popular aquaculture fish in China with high economic value in which male-biased sex dimorphism was observed in terms of body size and body weight. In this study, DNA methylation-sensitive RAD sequencing (Methyl-RAD) was used to explore the epigenetic difference between adult male and female samples in brain and gonad tissues. In brain tissues, 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Previous study also reported this pattern in gonad tissue of another sh with female-biased SSD, Cynoglossus semilaevis [36]. But no whole genome methylation difference was found in brain tissue between different sexes of Ussuri cat sh (Pseudobagrus ussuriensis), which might be caused by the tissue-speci c gene expression and regulation [25]. Differentially methylated gene analysis showed that there are 1,137 DMGs with more than 3…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous study also reported this pattern in gonad tissue of another sh with female-biased SSD, Cynoglossus semilaevis [36]. But no whole genome methylation difference was found in brain tissue between different sexes of Ussuri cat sh (Pseudobagrus ussuriensis), which might be caused by the tissue-speci c gene expression and regulation [25]. Differentially methylated gene analysis showed that there are 1,137 DMGs with more than 3…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we used MethylRAD to study the epigenetic difference between female and male liver tissue for Ancherythroculter nigrocauda, a sh with female-biased SSD. MethylRAD had been used in many epigenetic studies which aimed at nding methylation difference between various phenotypes [25,35]. It has many advantages compared with whole genome bisul te sequencing or reduced represented bisul te sequencing, such as it doesn't need to convert m C to T before library construction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such induced expression was found to be regulated by DNA methylation ( Veron et al, 2018 ). Similarly, reduced levels of methylation in the promoter regions of STAT3 and VEGFA genes were found to be correlated with their increased expression under hypoxic conditions ( Li et al, 2022a ).…”
Section: Review Of Recent Progress Of Genetic and Epigenetic Studies ...mentioning
confidence: 98%
“…Seven genes are involved in gene expression modulation and affect either DNA methylation, transcription, or alternative splicing. If fish, sex-specific methylation is known for its role in modulating the expression level of reproduction-related genes (Laing et al, 2018;Li, Chen, et al, 2022) and in sex determinism (Gemmell et al 2019). Similarly, sex-specific transcript usage can provide an alternative route from gene regulation to generate sexual dimorphism (Telonis- Scott et al, 2009;Naftaly et al, 2021).…”
Section: Sex-biased Genes Found In All Tissues Are Implicated In Cell...mentioning
confidence: 99%